2019
DOI: 10.1371/journal.ppat.1008121
|View full text |Cite|
|
Sign up to set email alerts
|

ALVAC-HIV B/C candidate HIV vaccine efficacy dependent on neutralization profile of challenge virus and adjuvant dose and type

Abstract: The ALVAC-HIV clade B/AE and equivalent SIV-based/gp120 + Alum vaccines successfully decreased the risk of virus acquisition in humans and macaques. Here, we tested the efficacy of HIV clade B/C ALVAC/gp120 vaccine candidates + MF59 or different doses of Aluminum hydroxide (Alum) against SHIV-Cs of varying neutralization sensitivity in macaques. Low doses of Alum induced higher mucosal V2-specific IgA that increased the risk of Tier 2 SHIV-C acquisition. High Alum dosage, in contrast, elicited serum IgG to V2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…As we have previously published (43), adjuvant choice also makes a difference in the elicitation of ADCC-capable antibodies. Recently, Schifanella et al showed adjuvant choice and concentration had a strong influence on outcome for ALVAC-HIV B/E-induced protection in macaques (44). The adjuvant used for RV144 was an aluminum hydroxide gel, while HTVN 702 used MF59, an oil-in-water emulsion.…”
Section: Discussionmentioning
confidence: 99%
“…As we have previously published (43), adjuvant choice also makes a difference in the elicitation of ADCC-capable antibodies. Recently, Schifanella et al showed adjuvant choice and concentration had a strong influence on outcome for ALVAC-HIV B/E-induced protection in macaques (44). The adjuvant used for RV144 was an aluminum hydroxide gel, while HTVN 702 used MF59, an oil-in-water emulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were challenged simultaneously over two consecutive days or on a single day when fewer than 24 animals remained uninfected. The subtype C SHIV-1157ipd3N4 virus was selected as a stringent challenge strain for its tier 2 neutralization profile, heterologous sequence to the vaccine immunogens, and resistance to vaccine-mediated immunity [ 21 , 22 ]. The sequence distance between gp145 and the challenge strain is comparable to that between two randomly selected sequences within an HIV-1 subtype.…”
Section: Resultsmentioning
confidence: 99%
“…ALFA is believed to be an improvement to the highly successful but proprietary AS04 adjuvant, which contains free MPLA adsorbed to alum, and neither of these have been assessed for vaccination against HIV-1. Protection was determined by limiting-dose serial intrarectal challenge with the heterologous, tier 2, CCR5-tropic subtype C SHIV-1157ipd3N4 virus strain, considered to be a stringent model with limited vaccine efficacy achieved to date [20][21][22]. Adjuvanting with ALFA, but not alum, dramatically reduced the per-exposure infection risk, however, protection was limited to male animals.…”
Section: Introductionmentioning
confidence: 99%
“…CCL2 is also induced by MVA [ 154 ], can be important for avoiding immunopathology [ 51 ], and is induced by the licensed adjuvants, Alum and MF59 [ 205 ]. CXCL10 is also induced by MVA [ 206 ] and by the licensed adjuvant, MF59 [ 207 ]. Given the extensive clinical safety record of MVA vaccination [ 208 ] and the lack of overt injection site reactogenicity or fever observed in NHPs after SCV-ZIKA/CHIK vaccination [ 22 ], CCL2 and CXCL10 up-regulation at the injection site would thus not appear to be compelling biomarkers for adverse events after MVA or SCV vaccination.…”
Section: Discussionmentioning
confidence: 99%